Assessing fatigue in women over 50 years with rheumatoid arthritis: a comprehensive case-control study using the FACIT-F scale - Valencia-Muntalà, Lidia; Gómez-Vaquero, Carmen; Berbel-Arcobé, Laura; Benavent, Diego; Vidal-Montal, Paola; Juanola, Xavier; Narváez, Javier; Nolla, Joan M. (Frontiers in Medicine, 2024)
Introduction Data on prevalence of fatigue in rheumatoid arthritis (RA) patients in the era of biological treatments remains scarce, with a lack of case-control studies. This study evaluates the prevalence of fatigue in Spanish women over 50 years with RA using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) scale, explores its association with RA-related variables, and seeks to identify the primary factors influencing fatigue. Ultimately, our objective is to underscore the clinical significance of fatigue as a comorbidity and to advocate for its systematic evaluation in routine clinical practice. Methods In a case-control study at a tertiary university hospital, 191 women over 50 years (mean age: 67.5 ± 8.8 years) meeting ACR 2010 criteria for RA and age-matched controls were assessed using the FACIT-F scale, SF-12 questionnaire, and RA-related clinical measures. Results Fatigue was significantly more prevalent in the RA group (61%) compared to controls (37%, p < 0.001), with RA patients showing lower mean FACIT-F scores (36.0 ± 10.6 vs. 40.0 ± 0.6, p < 0.001). Correlations were noted between FACIT-F scores and C-reactive protein, DAS28, RAPID3, HAQ, and SF-12 scores. A multivariate analysis was performed and four models generated. The final model, with an R2 of 0.817, indicates that fatigue is significantly influenced by disease activity (RAPID 3) and mental and physical health (SF12) and age, explaining 81.7% of the variance in fatigue. Conclusion Fatigue remains significantly prevalent and severe in women over 50 years with RA, strongly linked to disease activity, disability, and diminished quality of life. Systematic fatigue assessment and targeted strategies in clinical settings are essential to address this widespread issue. Future research should explore targeted interventions tailored to this demographic to enhance quality of care.